"The U'solia's And Akbaia's School And The End Of The Conflict By The Bahbahani At The End Of The Twelfth Century AH". - رزوقي, جواد رضا (Journal of College of Education, 2018)
The Emamei's school witnessed a major development in the process of devising Shari'a rulings from its original branches after the great backbiting 329 AH. This development took a gradual upward trend, which was the emergence of the fundamentalist school since the era of Sheikh Mufid. However, this fundamentalist school faced a great intellectual challenge in the eleventh century AH By the school of news founded by Mohammed Amin Estrabadi threatened to end the school of fundamentalism and the closure of the front school and its stagnant and ineffectiveness in front of religious issues developed for modern society, has prevailed this approach nearly two centuries and almost undermine the pillars of the fundamentalist approach to Lula The only success Bahbahani in addressing this school after the success of the efforts of fundamentalist jurists before him in the face of this trend. Because of this importance, this topic has been chosen as a title for research.            Certainly, there are many reasons for the spread of the doctrine of the Akhbaris in the scientific and religious centers in Iraq, Persia, Hijaz, Bahrain and other countries, foremost among which is the poor general situation witnessed by the Islamic countries and the nature of the conflicts witnessed in these countries, which took the nature of sectarian conflict, The growing sectarian and sectarian tensions. The radical news trend dominated most of the scientific cities of Al-Bayt School, and Karbala was the center of this trend, especially under the leadership of Yusuf Bahrani. The dominance of this trend has spread for almost two centuries, during which the fundamentalist approach has declined to the extent that fundamentalist books have touched the tissue of its impurity.